Thermal energy environment cycle based on virtual image technology application in urban green environment space planning and design - Li, Jiexu; Abdul Aziz, Faziawati; Shahidan, Mohd Fairuz (Elsevier Ltd, 2025)
This study discussed the application of thermal energy environmental cycle based on virtual image technology in urban green environment spatial planning and design, collected urban meteorological data, geographic information data and urban heat island effect related research data, and used virtual image technology to build a three-dimensional city model to simulate the thermal energy environmental cycle under different design schemes. The effect of urban heat island was simulated by computer simulation software, and the influence of different urban structure and greening on thermal energy environment was analyzed. According to the simulation results, the urban green space layout scheme was designed to optimize the circulation path of thermal energy environment. The results show that virtual image technology has high accuracy and practicability in simulating urban thermal environment. Through the simulation analysis, we found that urban green space layout, building height and density, and urban water body configuration have significant effects on the thermal energy environmental cycle. Based on these findings, the urban green space scheme designed can effectively alleviate the urban heat island effect and improve the quality of urban thermal environment. Therefore, the rational use of virtual image technology for urban planning can significantly improve the quality of urban thermal environment and provide strong support for urban sustainable development.